2021
DOI: 10.1039/d1nr01103k
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of intrinsic two-dimensional antiferromagnets from transition-metal borides

Abstract: Intrinsic two-dimensional (2-D) magnets are promising materials for developing advanced spintronic devices. Few have already been synthesized from the exfoliation of the van der Waals magnetic materials. In this work,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 70 publications
3
47
0
Order By: Relevance
“…2 Since then, 2D materials have attracted extensive interdisciplinary attention and many 2D materials were successfully fabricated, for example, hexagonal boron nitride, graphitic carbon nitride (g-C 3 N 4 ), elemental 2D nanosheets (2D-Xenes), transition metal dichalcogenides (TMD), transition metal carbides and borides (MXenes, MBenes). [3][4][5][6][7][8][9] Besides, the development of computing algorithms and facilities are signicantly accelerating the pace of the discovery of 2D materials. [10][11][12] In 2018, high-throughput calculations identied thousands of easily or potentially exfoliable three-dimensional (3D) layered compounds and more than 30 different prototypes in 2D crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…2 Since then, 2D materials have attracted extensive interdisciplinary attention and many 2D materials were successfully fabricated, for example, hexagonal boron nitride, graphitic carbon nitride (g-C 3 N 4 ), elemental 2D nanosheets (2D-Xenes), transition metal dichalcogenides (TMD), transition metal carbides and borides (MXenes, MBenes). [3][4][5][6][7][8][9] Besides, the development of computing algorithms and facilities are signicantly accelerating the pace of the discovery of 2D materials. [10][11][12] In 2018, high-throughput calculations identied thousands of easily or potentially exfoliable three-dimensional (3D) layered compounds and more than 30 different prototypes in 2D crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Spin-polarized density-functional theory (DFT) calculations were performed using the Vienna ab initio simulation package (VASP). , The Perdew–Burke–Ernzerhof (PBE) functional and projector augmented wave (PAW) potential , were adopted. According to the work of Wang et al and Ji et al, a Hubbard U eff = 3 eV applied to d orbitals is reliable to determine the magnetic ground state. To obtain more accurate magnetic parameters and electronic structures, the higher-level HSE06 functional containing the exact exchange energy was employed to obtain more accurate magnetic parameters and electronic structures.…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, their low Neél temperature and degradation in ambient conditions hinder their practical applications for spintronics in nanoscale. [7][8][9]13 Two-dimensional (2D) antiferromagnetic materials with roomtemperature T N have also been theoretically proposed, such as semiconducting FeAs-III (T N ∼ 350 K), 14 AMnBi (A = K, Rb, Cs, T N ∼ 300 K), 15 metallic Mn 2 C (T N = 720 K), 16 TMB (TM = Mn, Fe, T N = 300−320 K), 17 and MnX 2 S 4 (X = Al, Ga, T N = 549−702 K). 18 Nevertheless, antiferromagnetic nanosheets with both high T N and ambient stability are still rarely explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since Naguib et al first synthesized 2-D transition metal carbon/nitride materials (MXenes) in 2011, MXenes have attracted substantial interests and have been widely studied both experimentally and theoretically. MXenes can be fabricated by selectively etching A-layer of the MAX phase, , the ternary transition metal layered compounds, where M, A, and X represent an early transition metal, IIIA or IVA group element and C or N element, respectively. A variety of work have shown that MXenes have broad application potential in energy storage and photo/electrocatalysis, and so on Afterward, extensive application prospects of MXenes inspired people to explore in related fields. In 2015, Ade and Hillebrecht proposed that a series of ternary borides, which can be expressed as (MB) 2 Al y (MB 2 ) x , were closely similar to the group of ternary carbides or nitrides M n +1 AX n , so-called MAX phases, and named them as MAB phases . Furthermore, MBenes, an analog of MXenes, have been proposed experimentally and theoretically. Different from MAX phases, MAB phases belong to an orthorhombic space group (we use o -MAB for clarify). Because the anisotropy of the chemical bonding in o -MAB phases is not significant, the preparation of o -MBenes through selective etch has not successfully yet. , It is worth mentioning that in 2019, our group predicted the first hexagonal ternary phase Ti 2 InB 2 and removed Indium layer experimentally .…”
Section: Introductionmentioning
confidence: 99%